Fortunes of feminism: from state-managed capitalism to neoliberal crisis - Fraser, Nancy (London, 2013)
"Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.